1980
DOI: 10.1037/0021-843x.89.3.428
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of emotion recognition in schizophrenics.

Abstract: Forty-eight hospitalized schizophrenics and 48 nonhospitalized normals were administered a test of emotion recognition which included photographs depicting facial expressions of eight different emotions. The patient and normal groups were subdivided by age: children (8-12 years), adolescents (13-19 years), and adults (20-50 years). Patients and normals were matched on age, sex, and educational level. Normals were significantly better than schizophrenics at identifying all of the emotions. This difference held … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 11 publications
6
55
0
Order By: Relevance
“…Of the 81 non-overlapping studies that examined sex differences in FEP in schizophrenia included in Kohler et al [7] , Chan et al [5] , and Savla et al [9] , four studies examined sex differences in FEP in samples of either recent-onset schizophrenia or children and adolescents diagnosed with schizophrenia-spectrum disorders (these studies were not included in Barkl et al [30] ). Two studies did not find sex differences in FEP in children or adolescents diagnosed with schizophrenia [41,76] .…”
Section: Early and Recent-onset Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 81 non-overlapping studies that examined sex differences in FEP in schizophrenia included in Kohler et al [7] , Chan et al [5] , and Savla et al [9] , four studies examined sex differences in FEP in samples of either recent-onset schizophrenia or children and adolescents diagnosed with schizophrenia-spectrum disorders (these studies were not included in Barkl et al [30] ). Two studies did not find sex differences in FEP in children or adolescents diagnosed with schizophrenia [41,76] .…”
Section: Early and Recent-onset Schizophreniamentioning
confidence: 99%
“…Twenty-two studies examined sex differences in FEP in adult samples of chronically ill people with schizophrenia. The majority of these studies (n = 19) did not find sex differences in FEP, either on identification tasks [31][32][33][34][35][36][37][38][39][40][41] , discrimination tasks [42,43] , or in studies that included both task types [44][45][46][47][48][49] . Three studies included in Kohler et al [7] , Chan et al [5] , and Savla et al [9] found sex differences in FEP performance on identification tasks in adults with chronic schizophrenia.…”
Section: Adults With Chronic Schizophreniamentioning
confidence: 99%
“…schizophrenic, broadly defined ''anxious-depressed'') samples (e.g., Walker, 1981;Walker, Marwit, & Emory, 1980). In addition, children described as ''disordered'' and ''maladjusted'' (a) provide fewer appropriate examples of situations that would trigger emotions, (b) describe fewer cues for recognizing their own and others' emotions, and (c) exhibited a limited ability to use multiple cues (e.g., personal information) to infer another person's emotion (e.g., Meerum-Terwogt, 1990;Meerum-Terwogt, Schene, & Koops, 1990).…”
Section: Emotion Understanding: Psychopathological Populationsmentioning
confidence: 99%
“…Numerous reports over the last forty years (reviewed in Hellewell and Whittaker 1998) indicate that patients with schizophrenia have a deficit in properly recognizing facial affect-the emotional value aspects of facial expressions (Borod et al 1993;Streit et al 1997;Addington and Addington 1998;Federman et al 1998;Habel et al 2000;Izard 1959;Dougherty et al 1974;Muzekari and Bates 1977;Walker et al 1980;Heimberg et al 1992;Iscoe and Veldman 1963;Pillowski and Bassett 1980). Yet the neural correlates of these deficits have not been established.…”
mentioning
confidence: 99%